A Variety of Bond Analysis Methods, One Answer? An Investigation of the Element−Oxygen Bond of Hydroxides HnXOH. Issue 23 (6th April 2018) - Fugel, Malte; Beckmann, Jens; Jayatilaka, Dylan; Gibbs, Gerald V.; Grabowsky, Simon
Abstract: There is a great variety of bond analysis tools that aim to extract information on the bonding situation from the molecular wavefunction. Because none of these can fully describe bonding in all of its complexity, it is necessary to regard a balanced selection of complementary analysis methods to obtain a reliable chemical conclusion. This is, however, not a feasible approach in most studies because it is a time‐consuming procedure. Therefore, we provide the first comprehensive comparison of modern bonding analysis methods to reveal their informative value. The element−oxygen bond of neutral H n XOH model compounds (X=Li, Be, B, C, N, O, F, Na, Mg, Al, Si, P, S, Cl) is investigated with a selection of different bond analysis tools, which may be assigned into three different categories: i) real space bonding indicators (quantum theory of atoms in molecules (QTAIM), the electron localizability indicator (ELI‐D), and the Raub–Jansen index), ii) orbital‐based descriptors (natural bond orbitals (NBO), natural resonance theory (NRT), and valence bond (VB) calculations), and iii) energy analysis methods (energy decomposition analysis (EDA) and the Q‐analysis). Besides gaining a deep insight into the nature of the element−oxygen bond across the periodic table, this systematic investigation allows us to get an impression on how well these tools complement each other. Ionic, highly polarized, polarized covalent, and charge‐shift bonds are discerned from each other. Abstract : Find the balance : A variety of bond analysis methods is applied on the element−oxygen bond of H n XOH model compounds to probe the complementarity of the methods and to end up with a classification of different types of element−oxygen bonds (see figure).